Manajemen Strategi Pengembangan Kurikulum dan Interaksi Edukatif - Putra, Suntama; Yulaekah, Yulaekah; Syaifuddin, Muhammad; Andriani, Tuti (Dinasti Review, 2023)
The curriculum has a dynamic nature, from time to time it can change according to the current situation and conditions. Therefore, strategic curriculum management is needed in designing and developing curricula according to the needs of the times, one of which is by carrying out educative interaction learning. This research method uses Library Research or library research by collecting various kinds of data and literacy needed. The results of this study are that strategic management of curriculum development and educative interaction is needed in schools to achieve the vision, mission and goals of these educational institutions. In its implementation, it is necessary to pay attention to the goals and steps of curriculum development, namely: formulating instructional objectives, selecting learning experiences (selection of learning experiences), organizing learning experiences (organization of learning experiences), and evaluating (evaluating).